One-Stage Gender-Confirmation Surgery as a Viable Surgical Procedure for Female-to-Male Transsexuals. Issue 5 (1st May 2017) - Stojanovic, Borko; Bizic, Marta; Bencic, Marko; Kojovic, Vladimir; Majstorovic, Marko; Jeftovic, Milos; Stanojevic, Dusan; Djordjevic, Miroslav L.
Abstract: Background: Female-to-male gender-confirmation surgery (GCS) includes removal of breasts and female genitalia and complete genital and urethral reconstruction. With a multidisciplinary approach, these procedures can be performed in one stage, avoiding multistage operations. Aim: To present our results of one-stage sex-reassignment surgery in female-to-male transsexuals and to emphasize the advantages of single-stage over multistage surgery. Methods: During a period of 9 years (2007–2016), 473 patients (mean age = 31.5 years) underwent metoidioplasty. Of these, 137 (29%) underwent simultaneous hysterectomy, and 79 (16.7%) underwent one-stage GCS consisting of chest masculinization, total transvaginal hysterectomy with bilateral adnexectomy, vaginectomy, metoidioplasty, urethral lengthening, scrotoplasty, and implantation of bilateral testicular prostheses. All surgeries were performed simultaneously by teams of experienced gynecologic and gender surgeons. Outcomes: Primary outcome measurements were surgical time, length of hospital stay, and complication and reoperation rates compared with other published data and in relation to the number of stages needed to complete GCS. Results: Mean follow-up was 44 months (range = 10–92). Mean surgery time was 270 minutes (range = 215–325). Postoperative hospital stay was 3 to 6 days (mean = 4). Complications occurred in 20 patients (25.3%). Six patients (7.6%) had complications related to mastectomy, and one patient underwent revision surgery because of a breast hematoma. Two patients underwent conversion of transvaginal hysterectomy to an abdominal approach, and subcutaneous perineal cyst, as a consequence of colpocleisis, occurred in nine patients. There were eight complications (10%) from urethroplasty, including four fistulas, three strictures, and one diverticulum. Testicular implant rejection occurred in two patients and testicular implant displacement occurred in one patient. Clinical Implications: Female-to-male transsexuals can undergo complete GCS, including mastectomy, hysterectomy, oophorectomy, vaginectomy, and metoidioplasty with urethral reconstruction as a one-stage procedure without increased surgical risks and complication rates. Strengths and Limitations: To our knowledge, this is the largest cohort on this topic so far, with good surgical outcomes. Limitations include lack of selection or exclusion criteria and lack of other studies with a simple approach. For this reason, the technique should be studied further and compared with other techniques for female-to-male surgery before it can be recommended as an alternative procedure. Conclusions: Through a multidisciplinary approach of experienced teams, one-stage GCS presents a safe, viable, and time- and cost-saving procedure. Complication rates do not differ from reported rates in multistage surgeries.